The impact of a paradigm shift module based on cognitive behavioral therapy on the subconstructs of self-awareness, attitude, trait, and behavior among criminal offenders - Chiat, Lee Eng; Arip, Mohammad Aziz Shah Mohamed; Sa’ad, Fauziah Mohd (Psikohumaniora: Jurnal Penelitian Psikologi, 2025)
Recidivism remains a persistent challenge in criminal justice, highlighting the need for effective, evidence-based rehabilitation strategies. Despite current programs, many offenders relapse into criminal behavior due to unresolved psychosocial issues. This study examines the effectiveness of the Paradigm Shift Module (PSM), based on cognitive behavioral therapy (CBT), in enhancing self-awareness among criminal offenders—a key factor in behavioral transformation. A quasi-experimental design with pretest and posttest measures was employed. A total of 80 offenders were selected through purposive sampling and divided into two groups: a treatment group that received the PSM intervention and a control group with no intervention. The Paradigm Shift Instrument (PSI), developed by the researcher, was used to assess self-awareness across three subconstructs: attitude, trait, and behavior. The PSI demonstrated strong psychometric properties, with a content validity index (CVI) of ≥ 0.95 and a Cronbach’s alpha of .955. Statistical analysis, including paired sample t-tests and multivariate analysis of covariance (MANCOVA), revealed significant improvements in the treatment group. Attitude scores increased from M = 1.85 to M = 3.27 (t = -22.910, p < .05); trait from M = 1.89 to M = 3.23 (t = -20.916, p < .05); and behavior from M = 1.89 to M = 3.21 (t = -21.547, p < .05). The MANCOVA results confirm a significant treatment effect, while age and recidivism history showed no significant influence. The findings indicate that the PSM is a promising and effective intervention for fostering self-awareness, supporting rehabilitation, and reducing the likelihood of reoffending among incarcerated individuals.